Organic geochemical and palynological evidence for Holocene natural and anthropogenic environmental change at Lake Dojran (Macedonia/Greece). (August 2017) - Thienemann, Matthias; Masi, Alessia; Kusch, Stephanie; Sadori, Laura; John, Stephan; Francke, Alexander; Wagner, Bernd; Rethemeyer, Janet
In this study, we present lipid biomarker and palynological data for a sediment core from Lake Dojran (Macedonia/Greece), which covers the entire Holocene period. We analyzed vascular plant-derived n -alkanes, combustion-derived polycyclic aromatic hydrocarbons (PAHs), fecal steroids, and bacterial and archaeal glycerol dialkyl glycerol tetraether (GDGT) lipids in concert with microcharcoal and pollen assemblages to reconstruct climatic, environmental, and human impact in the Dojran catchment and the greater Dojran area. Overall, our results suggest a relationship between anthropogenic activity and environmental/climatic change since increased human impact corresponds to phases of higher humidity and high lake levels at Lake Dojran. During the early Holocene, the record reveals increasing temperatures and humidity and concurrent increasing vegetation cover and runoff/soil erosion, respectively. Following a thermal maximum during the middle early Holocene, temperatures decrease gradually until present. The middle-Holocene at Lake Dojran is characterized by relatively stable environmental conditions followed by greater climatic instability and strong anthropogenic overprint during the late-Holocene. The fecal stanol record reveals phases of increased human impact during the early Bronze Age, the late Bonze/early Iron Age, and the Middle Ages. A phase of low stanol and PAH concentrations from the late Iron Age until the early Middle Ages is either related to ecosystem changes and/or changes in settlement pattern since concurrent pollen data indicate intensified land use. Human impact re-intensified during the Middle Ages with some variability probably related to climatic variations of the 'Medieval Warm Period' and the 'Little Ice Age'.